Unwinding the Threads of Mesoporous Silica Nanoparticles as Cutting-edge for the Management of Inflammation: An Updated Review - Dhiman, Priya; Singh, Sukhbir; Arora, Sandeep; Sharma, Neelam; Gulia, Ritu; Kishore, Ladli (Current Pharmaceutical Biotechnology, 2025)
BackgroundInflammation serves as a protective response to combat cellular and tissue damage. There is currently a wide array of synthetic and traditional therapies available for the treatment of inflammatory diseases. However, it is necessary to create a drug delivery system based on nanotechnology that can improve the solubility, permeability, and bioavailability of current treatments. Mesoporous silica nanoparticles (MSNPs) are inorganic materials known for their organised porous interiors, high pore volumes, substantial surface area, exceptional selectivity, permeability, low refractive index, and customisable pore sizes.ObjectiveThis review offers concise insights into the progression of the pathophysiology of inflammation, as well as the inducers, mediators, and effectors that are involved in the inflammatory pathway. This study focuses on the growing significance of MSNPs in the treatment of neuroinflammation, inflammatory bowel disease, arthritic inflammation, lung inflammation, and wound healing applications. This review also presents the latest information on the crucial role of MSNPs in delivering herbal medicines for the treatment of inflammation.MethodsA comprehensive literature search was conducted for this aim, utilising the Google Scholar, PubMed, and ScienceDirect databases. A systematic review was undertaken utilising scholarly articles published in peer-reviewed journals from 2000 to 2024.ResultsThe inflammatory mediators involved in the pathophysiology of inflammation include platelet-activating factor, lipoxygenase, cyclooxygenase, Interferon-α, interleukin-6, interleukin-1β, matrix metalloproteinases, inducible nitric oxide synthase, nuclear factor-κB, prostaglandins, nitric oxide, and phospholipase A2. MSNPs have the potential to be used in the treatment of neuroinflammation, inflammatory bowel disease, arthritic inflammation, lung inflammation, and wound healing. The investigation of the MSNPs of plant-based compounds such as berberine, tetrahydrocannabinol, curcumin, and resveratrol has shown successful results in recent years for the purpose of managing inflammation.ConclusionThis review demonstrates that MSNPs have a strong potential to play a positive role in delivering synthetic and plant-based therapies for the treatment of inflammatory illnesses.
Keywords: Mesoporous silica nanoparticles